Strukturelle Neuroplastizität und motorisches Lernen - Taubert, M. (Leipziger Sportwissenschaftliche Beiträge, 2011)
Recent findings in neuroscience suggest that human brain structure changes in response to environmental alterations and skill learning. Whereas much is known about structural changes after intensive practice for several months, little is known about the effects of single practice sessions on macroscopic grey and white matter changes and about progressive (dynamic) morphological alterations relative to improved task proficiency during learning for several weeks. Using T1-weighted and diffusion weighted imaging in humans, we demonstrated significant grey matter alterations in frontal and parietal brain areas following only two sessions of practice in a complex stabilometer balancing task (Taubert et al., 2010). Grey matter changes in the prefrontal cortex correlated positive with subject`s performance improvements during a six weeks learning period. Furthermore, we found that microstructural changes of fractional anisotropy in corresponding white matter regions followed the same temporal dynamic in relation to task performance. The results make clear how marginal alterations in our ever changing environment affect adult brain structure and elucidate the interrelated reorganization in cortical areas and associated fibre connections in correlation with improvements in task performance.